ANALISIS PUTUSAN NOMOR 574K/PID.SUS/2018 MENGENAI PELANGGARAN PASAL 27 AYAT (1) UNDANG-UNDANG NOMOR 11 TAHUN 2008 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK - Pelemon Siagian; Sugandi Ishak (Jurnal Hukum Adigama, 2019)
Baiq Nuril Maknun is accused of violating Article 27 paragraph (1) of Law Number 11 Year 2008 concerning Information and Electronic Transactions (UU ITE). In the Mataram District Court found not proven guilty, the Public Prosecutor filed an appeal with Decision Number 574K / Pid. Sus / 2018 and the Supreme Court (MA) sentenced him guilty to Baiq Nuril Maknun with 6 month prisons sentence and a Rp. 500 million. Baiq Nuril Maknun then submitted a Review (PK) with Decision Number 83PK / Pid.Sus / 2019 and the Supreme Court rejected the PK proposed by Baiq Nuril Maknun. Method research used in writing this thesis is normative legal research. The results showed that Baiq Nuril Maknun submitted an amnesty request to President Joko Widodo and was granted, Baiq Nuril Maknun was free from the snares of the law. Submission of amnesty must be selective and for certain cases that are felt by the general public, the court's decision must be able to reflect justice because it is in accordance with the Judicial Act and the Supreme Court, and judges are required to explore the values of justice in society.